Going ape - Sutton, Laurie S. (I can read! Reading with help, 2012)
"The Gotham City Zoo has gone bananas! With Gorilla Grodd on the loose, Batman and Superman must join forces to put an end to the monkey business and save Gotham City"--p. [4] of cover.